Comprehensive rotorcraft aeroacoustics: investigation of surface pressure distribution methods for rotor noise - Şenipek, M.; Yücekayali, A.; Özyörük, Y. (My University, 2019)
Having full helicopter trim capability, comprehensive codes are indispensable for helicopter aeromechanics yet they operate over spanwise concentrated aerodynamic loads calculated at blade segment aerodynamic centers. In this study, an approach to generate distributed aerodynamic loads from comprehensive models, over real blade geometry for further aeroacoustic calculations of a helicopter rotor is proposed. Distribution of concentrated aerodynamic loads over upper and lower surface of the blade geometry with the help of an airfoil pressure database to prepare higher resolution data for acoustic solvers is studied. In order to assess the improvement, first, the concentrated aerodynamic loads are distributed over two-dimensional representative upper and lower surfaces then over three-dimensional blade geometry and acoustic signatures are compared with each other, HART-II wind tunnel test data and benchmark tool PSU-WOPWOP.